1998
DOI: 10.1111/j.1460-9568.1998.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic stimulation of MHC class I and IRF‐1 gene expression by IFN‐γ and TNF‐α in oligodendrocytes

Abstract: In order to understand the molecular basis of the synergistic action of interferon gamma (IFN-gamma) and tumour necrosis factor alpha (TNF-alpha) on rat oligodendrocyte development, we studied some aspects of the signalling pathways involved in the regulation of the major histocompatibility complex (MHC) class I and the interferon regulatory factor 1 (IRF-1) gene expression. Two well-defined inducible enhancers of the MHC class I gene promoter, the MHC class I regulatory element (MHC-CRE) and the interferon co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
9

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 70 publications
0
15
0
9
Order By: Relevance
“…TNFR1 expression is upregulated by ATRA and ATRA-cationic liposome/IL-12 pDNA complexes in mice P Charoensit et al cytokines such as interferon-g and IL-1b. 22,37,38 Therefore, ATRA-cationic liposome/IL-12 pDNA complexes may produce synergistic effects on TNFR1 upregulation. To date, the upregulation of TNFR1 by ATRA has been reported in human lung cancer cells; 22 however, there have been no reports in mouse colon26 cells.…”
Section: Discussionmentioning
confidence: 99%
“…TNFR1 expression is upregulated by ATRA and ATRA-cationic liposome/IL-12 pDNA complexes in mice P Charoensit et al cytokines such as interferon-g and IL-1b. 22,37,38 Therefore, ATRA-cationic liposome/IL-12 pDNA complexes may produce synergistic effects on TNFR1 upregulation. To date, the upregulation of TNFR1 by ATRA has been reported in human lung cancer cells; 22 however, there have been no reports in mouse colon26 cells.…”
Section: Discussionmentioning
confidence: 99%
“…13 In support of this, Deckert-Schluter et al 8 also demonstrated that TNF mRNA was not induced in the IFN-␥-deficient mice with Toxoplasma encephalitis. A recent study suggesting that induction of TNFR1 by IFN-␥ facilitates the actions of TNF-␣ at the transcription level shows the importance of this finding in oligodendrocytes, 14 although it is not unlikely that brain endothelial cells may respond in a similar manner. Agresti et al 14 demonstrated that neither IFN-␥ nor TNF-␣ was capable of inducing MHC class I regulatory element (MHC-CRE) binding activity when administered alone.…”
Section: Synergistic Actions Of Cytokinesmentioning
confidence: 94%
“…Einfluss von IFN-γ auf Oligodendrocyten-Vorläuferzellen potenzierenden Effekt von TNF-α feststellen konnten [Agresti et al, 1998;Andrews et al, 1998] [Boehm et al, 1997]. Aber auch Makrophagen [Munder et al, 1998], B-Zellen [Yoshimoto et al, 1997] und CD8a+ dendritische Zellen [Ohteki et al, 1999] können nach Aktivierung IFN-γ produzieren.…”
Section: Rolle Des Tnf-α Für Myelin Und Oligodendrocytenunclassified
“…Die Signalweiterleitung beider Cytokine könnte dann zu einer erhöhten Aktivierung des MHC Klasse I Genes führen [Agresti et al, 1998]. In einer Reihe von demyelinisierenden Krankheiten wurde eine anormale Expression dieses Genes beobachtet [Traugott 1987;Traugott and Lebon 1988].…”
Section: Rolle Des Tnf-α Für Myelin Und Oligodendrocytenunclassified
See 1 more Smart Citation